Early Fibrinolysis as Effective as Primary PCI When Reperfusion Delay is Long - Kuznar, Wayne (MD Conference Express, 2013)
Fibrinolytic therapy coupled with timely coronary angiography results in effective reperfusion in patients with ST-segment elevation myocardial infarction who cannot undergo primary percutaneous coronary intervention within 1 hour of presentation, according to the results of the Strategic Reperfusion (With Tenecteplase and Antithrombotic Treatment) Early After Myocardial Infarction trial [STREAM; Armstrong PW et al. N Engl J Med 2013].